On Short Sums Involving Fourier Coefficients of Maass Forms - Jääsaari J (UNIV BORDEAUX, INST MATHEMATIQUES BORDEAUX, 2025)
We study sums of Hecke eigenvalues of Hecke-Maass cusp forms for the group SL(n, Z), with general n >= 3, over short intervals of certain length under the assumption of the generalised Lindelof hypothesis and a slightly stronger upper bound concerning the exponent towards the Ramanujan-Petersson conjecture than is currently known. In particular, in this case we evaluate the second moment of the sums in question asymptotically.